Medial Approach to the Sciatic Nerve at the Popliteal Fossa in the Supine Position with Ultrasound Guidance and Nerve Stimulator. (29th March 2012) - Yanaru, Tomoaki; Shigematsu, Kenji; Higa, Kazuo; Nakamori, Erisa; Nitahara, Keiichi
Abstract : Ultrasound guided sciatic nerve block (SNB) at the popliteal fossa is performed with the lateral approach in the supine position or with the lateral or posterior approach in the prone position. When the sciatic nerve (SN) is blocked with the lateral approach in the supine position, the lower limb must be sufficiently elevated to enable adequate space around the knee joint for transducer application. When the SN is blocked in the prone position, the patients' position needs to be changed. We report a medial approach to the SNB at the popliteal fossa in the supine position with ultrasound guidance. Ten patients scheduled for elective knee or foot surgery participated in this study. Patients were placed in the supine position, with the hip and knee on the operated side flexed and the thigh externally rotated at approximately 45 degrees. A block needle was inserted in-plane with the transducer toward the SN bifurcation from the medial side of the thigh. The block performance time for SNB was 1.8 ± 0.5 min (1.3–3.1 min). All blocks were effective. Our medial approach to the SN in the supine position with ultrasound guidance does not require elevation of the patient's lower limb or a change in the patient's position.